In vivo effectiveness and safety of probiotics on prophylaxis and treatment of oral candidiasis: a systematic review and meta-analysis - Lijun Hu; Mimi Zhou; Andrew Young; Weiwei Zhao; Zhimin Yan (BMC, 2019)
Abstract Background To systematically review and assess the in vivo effectiveness and safety of probiotics for prophylaxis and treating oral candidiasis. Methods A literature search for studies published in English until August 1, 2018 was conducted in the following databases: PubMed, EMBASE, Cochrane Library, and Web of Science. Randomized controlled clinical trials and experimental mouse animal model studies comparing probiotics (at any dosage and in any form) with control groups (placebo, blank control or other agents) and reporting outcomes of the prophylactic and therapeutic effects were considered for inclusion. A descriptive study and, potentially, a meta-analysis were planned. Results Six randomized controlled clinical trials and 5 controlled experiments of mouse animal models were included in the systematic review. Four randomized controlled clinical trials comparing a probiotics group with a placebo/blank control group in 480 elderly and denture wearers were included in the meta-analysis. The overall combined odds ratio of the (random effects) meta-analysis was 0.24 (95% CI =0.09-0.63, P < 0.01). The overall combined odds ratio of the (fixed effects) sensitivity analysis was 0.39 (95% CI =0.25-0.60, P < 0.01) by excluding a study with the smallest sample size. These analyses showed that there was a statistically significant difference in the effect of probiotics compared with the control groups in elderly and denture wearers. The remaining 2 studies compared probiotics with other agents in a population aged 18-75 years and children aged 6-14 years respectively, and were analyzed descriptively. Meta-analysis and descriptive analyses indicated that probiotics were potentially effective in reducing morbidity, improving clinical symptoms and reducing oral Candida counts in oral candidiasis. The biases of the included studies were low or uncertain. The relatively common complaints reported were gastrointestinal discomfort and unpleasant taste, and no severe adverse events were reported. Conclusions Probiotics were superior to the placebo and blank control in preventing and treating oral candidiasis in the elderly and denture wearers. Although probiotics showed a favorable effect in treating oral candidiasis, more evidence is required to warrant their effectiveness when compared with conventional antifungal treatments. Moreover, data on the safety of probiotics are still insufficient, and further research is needed.